2009
DOI: 10.1016/j.bpj.2008.12.2918
|View full text |Cite
|
Sign up to set email alerts
|

TRPC Channels Function Independently Of STIM1 And Orai1

Abstract: Recent studies have defined roles for STIM1 and Orai1 as calcium sensor and calcium channel, respectively, for Ca 2+ -release activated Ca 2+ (CRAC) channels, channels underlying store-operated Ca 2+ entry (SOCE). In addition, these proteins have been suggested to function in signalling and constructing other channels with biophysical properties distinct from the CRAC channels. Using the human kidney cell line, HEK293, we examined the hypothesis that STIM1 can interact with and regulate members of a family of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 71 publications
1
49
1
Order By: Relevance
“…The rearrangement of microtubules in the regulation of SOCE has also been demonstrated by the application of colchicine [54][55][56], however, colchicine has no effect on TG-induced STIM1 movement. In addition, disruption of lipid rafts in the PM does not change the STIM1 movement [57].…”
Section: Discussionmentioning
confidence: 99%
“…The rearrangement of microtubules in the regulation of SOCE has also been demonstrated by the application of colchicine [54][55][56], however, colchicine has no effect on TG-induced STIM1 movement. In addition, disruption of lipid rafts in the PM does not change the STIM1 movement [57].…”
Section: Discussionmentioning
confidence: 99%
“…Store depletion promoted the recruitment of STIM1 to ER structures facing lipid raft domains enriched in the TRPC (canonical transient receptor potential) 1 cation channel, and both SOCE and STIM1 puncta formation were prevented by the disruption of lipid rafts with methyl-β-cyclodextrin or Filipin-III [55]. The involvement of TRPC channels in SOCE is still controversial, with several groups reporting that TRPC channels interact with STIM1 and/or with Orai channels and therefore contribute to SOCE influx [56,57], and others claiming that TRPC channels function independently of STIM and Orai [58]. Membrane lipid rafts may act as a switching platform that convert TRPC channels from receptor-operated channels into storeoperated channels by favouring their interaction with cortical ER structures enriched in STIM1 and facing the lipid rafts [59].…”
Section: Morphological Changes Associated With Soce Activationmentioning
confidence: 99%
“…Neutrophil motility and migration is dependent on elevations in [Ca 2+ ] i , and in FMLP-stimulated neutrophils, inhibition of MLCK by ML-9 decreases cell motility [14]. In a variety of cultured cell lines and endothelial cells, it has been demonstrated that ML-9 inhibits thapsigargin induced Ca 2+ release and hence SOCE [15][16][17][18]. Recently, using human neutrophils, we demonstrated that ML-9 inhibits Ca 2+ influx stimulated by thapsigargin but not by the agonists FMLP, PAF, or LTB 4 [7].…”
Section: Ml-9 Reveals Differences Between Soce and Roce In Neutrophilsmentioning
confidence: 99%